P05.76 Resuming treatment with immune checkpoint inhibitors in cancer patients who developed immune-related meningitis. (19th September 2018) - Cuzzubbo, S; Ursu, R; Mazoyer, J; Belin, C; Baroudjian, B; Lebbe, C; Carpentier, A
Abstract: Background: Immune checkpoint inhibitors (ICIs) targeting CTLA-4 (Cytotoxic T-lymphocyte associated antigen 4) and PD-1 (Programmed cell death ligand 1) constitute a promising class of cancer treatment but are associated with several immune-related disorders, including neurological syndromes. Several guidelines are available for the acute management of immune-related adverse events, but their long-term management is less clear and uniform, particularly concerning the duration of the steroid treatment and the safety of a re-introduction of ICI treatment. Material and Methods: We collected the cases of immuno-related meningitis associated with ICIs admitted to our department. Diagnosis was defined by a (1) high count of lymphocytes (>8 cells/mm3), without bacteria or virus detection, associated or not to a high level of proteins in cerebrospinal fluid; and (2) normal brain and spine imaging. After diagnosis, patients were followed by a neurologist until 1 year after meningitis onset to better define the steroids doses and the safety of ICI reintroduction in each case. Results: We here report 5 cases of meningitis related to ICIs. Delay of meningitis onset after ICI start was short (within 2 weeks) for 3 patients and relatively longer for the other 2 patients (7 and 13 weeks respectively). Steroid treatment was introduced in 4 patients at the dose of 1 mg/Kg, allowing a complete recovery within 2 weeks. Corticosteroids were gradually tapered until discontinuation after 1–3 months. The 5th patient spontaneously improved within 2 weeks. Given the favorable outcome, ICI drug was reintroduced in 4 patients, and none of them did show meningitis recurrence. In 2 patients, nevertheless, other severe immune-related adverse events occurred (tubulointerstitial nephritis and diffuse pneumonia) leading to the discontinuation of ICI. In both patients, ICIs was reintroduced early post discontinuation (3 and 4 weeks, vs 8 and 53 weeks in the 2 other cases). Conclusion: Cases of meningitis related to ICIs are rarely reported and poorly described in literature. In our cases, a steroid treatment is effective and generally necessary. ICI treatment discontinuation is not mandatory in case of isolated meningitis. However, a careful analysis of the benefit/risk ratio should be done on a case by case basis.